'We have to make an effort with it': Exploring the use of stages to help understand the personal information management needs of humanities and social science doctoral students managing dissertation information. (March 2017) - Cushing, Amber L.; Dumbleton, Odile
Fifteen doctoral students enrolled in a variety of humanities and social science programmes from a single metropolitan university in Ireland discussed their practices and habits associated with personal information management via three focus groups, in order to explore personal information management skills at different stages of the doctoral programme. Findings suggest that personal information management needs of doctoral students managing dissertation/thesis information can be categorised as three distinct stages: beginning, middle and end of the doctoral programme. In developing services to meet the needs of this population, information professionals may find it useful to classify such services via these three stages.